EP1210 Follow-up in gynecologic malignancies, correspondence with ESGO Guidelines- preliminary result of ENYGO survey. (1st November 2019) - Selcuk, I; Lanner, M; Pletnev, A; Vlachos, D; Nikolova, T; Lindquist, D; Zalewski, K
Abstract : Introduction/Background: To identify the follow-up strategies of gynecologic malignancies across Europe and compare the correspondence with ESGO Guidelines. Methodology: In 2019, a web-based survey was sent to the National Representatives of European Network of Young Gynae-Oncologists (2017–2019). The questionnaire consists of the questions related with vulvar cancer, cervical cancer, endometrial cancer and ovarian cancer. Results: A total of 15/31 (48.3%) National Representatives responded the survey. Despite having a national guideline (>50%), the topic of follow-up was missing in some countries. The follow-up was mainly led by clinicians and performed by gynecologic oncology team (table 1). For each malignancy, gynecologic examination is performed at every visit. Responders stated that Pap-test is routinely performed during the follow-up of cervical cancer 8/8 (100.0%), additionally in endometrial cancer 4/7 (57.1%) of responders perform routine Pap-test. Serum Ca-125 level is never routinely preferred during the follow-up of endometrial cancer, however serum Ca-125 is mostly preferred routinely for ovarian cancer. Complete blood count-biochemical tests and chest X-ray are not routine tests to consider at every visit. Routine imaging is mostly preferred for ovarian cancer and computed tomography is the most common imaging technique in case of a suspicion of recurrence except vulvar cancer in which magnetic resonance imaging is preferred (table 2). Conclusion: This preliminary results indicated that follow-up periods are similar with ESGO Guidelines. One of the major differences is that cytology is not recommended after radical/simple hysterectomy or chemoradiation in cervical cancer and the other one is serum Ca-125 is not a reliable marker in non-High grade serous carcinoma of the ovary. ESGO Guidelines generally don't recommend routine imaging unless a clinically indicated situation. Finally, these preliminary results showed that majority of the responses are similar with ESGO Guidelines. Disclosure: Nothing to disclose